ANALISIS SEKTOR BASIS DAN KONTRIBUSI SEKTOR PERTANIAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI KABUPATEN DAIRI - Rahmanta Ginting (Quantitative Economics Journal, 2015)
The agriculture sector is one sector of the economy given a priority in regional development, it’s because most of the population dependent on the sector and asource of income for the majority of the population, thus it’s no wrong if theagriculture sector serves as a support the regional development. The agriculture sector in the district Dairi consists of food crops and horticulture, plantation,animal husbandry, foresty, and fishery. Therefore, the purpose of this study is toanalyze the basis sector and agriculture sector contribution to the gross regionaldomestic product in the district Dairi. This study uses secondary data sourcedform of time series data from 2009 – 2013. The analysis model is a LocationQuotient (LQ) and sector contribution to gross regional domestic product in district Dairi. The result showed that the agriculture sector and the services is abasis sector or have a high role in a local economy. It is characterized by LQ isgreather than one, while other sectors are non basis sector because it has a LQ value smaller than one. In 2013, the agriculture sector provides the largestcontribution in gross regional domestic product structure in the district Dairi is58,47%.